Existence of Iterative Cauchy Fractional Differential Equation - Rabha W. Ibrahim (Journal of Mathematics)
Our main aim in this paper is to use the technique of nonexpansive operators in more general iterative and noniterative fractional differential equations (Cauchy type). The noninteger case is taken in sense of the Riemann-Liouville fractional operators. Applications are illustrated.